Service Quality of Local Government and Citizens’ Satisfaction - Saud, Dhan Bahadur (The Management Review, 2026)
This study explores the relationship between service quality and citizen satisfaction in the local governments of Kanchanpur District, Nepal, to understand how different dimensions of service quality influence public perceptions of local government services. The study incorporated a descriptive research design and collected data from 450 citizens selected through purposive and cluster sampling techniques from various municipalities and rural municipalities of Kanchanpur District. Primary data were gathered using structured questionnaires distributed physically among the respondents. The study indicates that reliability and assurance have a positive and significant relationship with citizen satisfaction, suggesting that citizens value dependable services and the confidence provided by local government officials. Though, responsiveness and empathy were found to have negative and statistically insignificant relationship with citizen satisfaction. The study emphasizes only on the local governments of Kanchnapur District, and further research could extend this analysis to other sectors such as banking, hospital, manufacturing and other non-governmental organizations to better understand the broader impact of service quality on customer or citizen satisfaction.